Giving Voice to the Forgotten: An Examination of the Music and Culture of Veljo Tormis's "Forgotten Peoples" Collection - Jones, Erik Reid (2006)
Veljo Tormis's development as a composer was influenced by the political climate in which he was raised. He was born into a flowering and independent Estonia, with a parliamentary system of government and a people developing their own sense of individual culture after winning independence from Russia in 1920. Unfortunately, when Tormis was ten years old, this national independence and stability fell apart. Estonia would not regain its independence until 1991, when Tormis was 61. This combination of foreign occupying powers would have a significant impact on Tormis's musical life and direction. That a people can be subsumed into a larger population might have been one of the driving factors that led Tormis to go beyond Estonia and study the music of the ancient cultures that surround his homeland. These Baltic Finns include (by his definition) the peoples surrounding the Gulf of Finland, the Gulf of Riga, and the eastern shore of the Baltic Sea. This includes Latvia, Estonia, some of far western Russia and portions of southern and eastern Finland. Out of these explorations came six cycles of a cappella choral music set to the music and languages of mostly dying cultures, in a collection called "Forgotten Peoples". This purpose of this project is to make the "Forgotten Peoples" collection more accessible to performers and listeners. First we will examine the history, culture, and language of the six different peoples, especially among those areas where they share commonalities. Next, we will do a lyrical analysis of the pieces, pointing out stylistic traits that are common in Balto-Finnic poetry. Finally, we will take an analytical look at the construction of many of the movements in the "Forgotten Peoples" collection.